(untitled) (Research, Society and Development, 2024)
Introduction: pain represents a frequent consequence, both of the cancer pathological process and its treatment. Oncological pain management requires a multidisciplinary and integrated approach, ensuring individualized care and continuous supervision, as the vast majority of patients require opioid use. Objective: to analyze the role of opioids in different strategies for managing oncological pain in palliative care patients. Methodology: this is a integrative literature review. Results: twenty studies were selected for the composition of this study, covering 10 different countries and various methodologies, including cross-sectional studies, randomized trials, cohort studies, and case series. Discussion: pain is a common complaint among oncology patients in palliative care. Clinical protocols recommend opioid use as first-line analgesia in severe cases, with the possibility of adjusting and escalating treatment as needed. Additionally, other drugs are being tested as adjuvants, which may improve the pain management experience. Final considerations: palliative care is essential in cancer management, aiming to improve the quality of life for patients and their families. An integrated and multidisciplinary approach is necessary to manage oncological pain, considering its various impacts. Adjustments in opioid dosage and the use of other medication classes are being investigated to enhance pain relief.